Multiple Non-Equivalent Interfaces Mediate Direct Activation of GABAA Receptors by Propofol - M. Eaton, Megan; L. Germann, Allison; Arora, Ruby; Q. Cao, Lily; Gao, Xiaoyi; J. Shin, Daniel; Wu, Albert; C. Chiara, David; B. Cohen, Jonathan; Henry Steinbach, Joe; S. Evers, Alex; Akk, Gustav (Current Neuropharmacology, 2016)
Background: Propofol is a sedative agent that at clinical concentrations acts by allosterically activating or potentiating the γ-aminobutyric acid type A (GABAA) receptor. Mutational, modeling, and photolabeling studies with propofol and its analogues have identified potential interaction sites in the transmembrane domain of the receptor. At the
Keywords: propofol